1978
DOI: 10.1017/s0081305200014060
|View full text |Cite
|
Sign up to set email alerts
|

Location Determinants of Manufacturing Industry in Rural Areas

Abstract: The spatial distribution of economic activity has been the subject of much theoretical study during the last 150 years. The two-state study which provides primary evidence for this article is, to the authors' knowledge, the first attempt to analyze statistically the determinants of industrial location in rural communities with an explicit objective of more enlightened public action at the local, state, and federal levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 6 publications
1
40
0
Order By: Relevance
“…At the micro level, Dorf and Emerson (1978) concluded that access to an interstate highway does not necessarily attract small to medium businesses. Smith, Deaton, and Kelch (1978), on the contrary, found that interstate-highway access does attract firms. There are also exceptions to the importance of highways: Kuehn and West (1971) found that highways primarily influence regional supply conditions and that they are not critical factors in economic development.…”
Section: Economic Growth or Declinementioning
confidence: 92%
“…At the micro level, Dorf and Emerson (1978) concluded that access to an interstate highway does not necessarily attract small to medium businesses. Smith, Deaton, and Kelch (1978), on the contrary, found that interstate-highway access does attract firms. There are also exceptions to the importance of highways: Kuehn and West (1971) found that highways primarily influence regional supply conditions and that they are not critical factors in economic development.…”
Section: Economic Growth or Declinementioning
confidence: 92%
“…Yet, Smith, Deaton, and Kelch (1978) found that access to highways did increase the likelihood of a firm moving to an area, although several other variables such as site-specific characteristics and the quality of fire protection had greater influence than highway access. In a study of rural Missouri, Kuehn, Braschier, and Shonkwiler (1979) found sufficient evidence to suggest that access to a quality water system played an important role in plant location.…”
Section: Is There a Link Between Investment And Growth And Development?mentioning
confidence: 94%
“…The common perception is that investment in public infrastructure sets the cornerstone for economic growth and development. Numerous studies purport to have revealed empirical relationships between investments in public infrastructure and economic development and growth (e.g., Aschauer, 1993;Humphrey & Sell, 1975;Kusmin, Redman & Sears, 1996;Smith, Deaton, & Kelch, 1978;Steinnes, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Yet its strategies are often stated in universal terms-at a community level-even when variability is assumed across different groups within the community. These tensions are particularly acute in highly diverse rural populations (see Christenson, 1980Christenson, , 1989Summers, 1986) where community development efforts have typically meant rural industrialization (Deaton, 1981;Dorf & Emerson, 1978;Kuehn, Braschler, & Shonkwiler, 1979;Lloyd & Wilkinson, 1985;Luloff & Chittenden, 1984;Smith, Deaton, & Kelch, 1978;Summers, 1986;Till, 1981;Williams, Sofranko, & Root, 1977), and to a lesser extent, attracting retirees Downloaded by [Anadolu University] at 19:46 26 December 2014 (Bender et al, 1985;Brown, 1988;Brown & Deavers, 1987;Cook, 1990;Glasgow, 1990;Glasgow & Beale, 1985;Gardner, 1988;Pulver, 1986;Summers & Hirsch', 1985). Christenson and Robinson (1989, P. ix, 3-our emphasis) define the concept of community development in the following way:…”
Section: Defining and Applying Community Development In A Highly Divementioning
confidence: 99%